2010
DOI: 10.1186/1471-2121-11-4
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of endocytic trafficking of transferrin receptor by optineurin and its impairment by a glaucoma-associated mutant

Abstract: BackgroundOptineurin is a multifunctional protein involved in several functions such as vesicular trafficking from the Golgi to the plasma membrane, NF-κB regulation, signal transduction and gene expression. Mutations in optineurin are associated with glaucoma, a neurodegenerative eye disease that causes blindness. Genetic evidence suggests that the E50K (Glu50Lys) is a dominant disease-causing mutation of optineurin. However, functional alterations caused by mutations in optineurin are not known. Here, we hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
125
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(138 citation statements)
references
References 55 publications
12
125
0
1
Order By: Relevance
“…1H,I). Previously, it has been shown that optineurin is present in vesicles positive for TfR (Nagabhushana et al, 2010;Park et al, 2010). Hence, we examined the distribution of TfR in the cells co-expressing optineurin and TBC1D17.…”
Section: Optineurin Interacts With a Non-catalytic Region Of Tbc1d17mentioning
confidence: 95%
See 1 more Smart Citation
“…1H,I). Previously, it has been shown that optineurin is present in vesicles positive for TfR (Nagabhushana et al, 2010;Park et al, 2010). Hence, we examined the distribution of TfR in the cells co-expressing optineurin and TBC1D17.…”
Section: Optineurin Interacts With a Non-catalytic Region Of Tbc1d17mentioning
confidence: 95%
“…It is involved in regulating many cellular functions such as vesicular trafficking from the Golgi to plasma membrane (Sahlender et al, 2005), endocytic trafficking (Au et al, 2007;Nagabhushana et al, 2010) and signaling leading to NF-kB activation (Nagabhushana et al, 2011;Zhu et al, 2007). Mutations in optineurin are associated with certain glaucomas and amyotrophic lateral sclerosis (Maruyama et al, 2010;Rezaie et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…TGN46 (marker for the Golgi) positive vesicles and recycling endosomes, while an UBD-mutated form of Optn (D474N) was redistributed into a cytosolic-like staining pattern. 42,78 The observation that the ubiquitin-binding activity of Optn is necessary for its localization to the Golgi apparatus suggests that, in addition to its interaction with Rab8, interaction with an ubiquitinated protein is important for this localization. 42 This protein could be Htt, since it is constitutively ubiquitinated and binds to a region of Optn encompassing its UBD.…”
Section: Optn and Diseasesmentioning
confidence: 99%
“…24,80 The ubiquitin-binding function of Optn is also important for antiviral immune response, selective autophagy of cytosolic bacteria and Transferrin receptor (TfR) recycling. 43,55,78 However, the role of Ub-binding activity in some Optn-mediated functions, such as the transport of lysosomal proteins, remains to be determined. Since ubiquitination of NEMO was shown to be important for NFκB activation, ubiquitination of Optn may also be important for its subcellular localization and functions.…”
Section: Optn and Diseasesmentioning
confidence: 99%
“…3). These data indicate that ␣-tocopherol is trafficked through the recycling endosomes: vesicles that replenish the plasma membrane with recycled receptors and some endocytic cargo and are controlled by Rab8 and its downstream effectors (51,53). To our surprise we found that in live cells, ␣-tocopherol is also located in lipid droplets, marked by the neutral lipid stain Nile red (Fig.…”
Section: Discussionmentioning
confidence: 67%